2016
DOI: 10.31018/jans.v8i3.1019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of partial replacement of fishmeal with Eichhornia crassipes on growth and survival of Labeo rohita (Hamilton, 1822) juveniles

Abstract: The objective of the study was to find out the effect of partial replacement of fish meal in the diet of Labeo rohita juveniles. In this experiment, the data pertaining to growth, survival rate, feed conversion ratio, protein efficiency ratio of L. rohita at partial replacement of fishmeal with E. crassipes were evaluated. For that purpose fry of approximately equal weight (57.97mg ± 1.25) were distributed in groups of 15 to each four aquaria at 0% (T1), 10% (T2), 20% (T3), 30% (T4) and 40% (T5) inclusion lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…The results of the present study are congruent with those of other researchers who have suggested that fish meal can partially be replaced with aquatic macrophytes [8,[44][45][46][47][48][49]. The results of the growth characteristics and feed consumption of C. carpio var.…”
Section: Discussionsupporting
confidence: 92%
“…The results of the present study are congruent with those of other researchers who have suggested that fish meal can partially be replaced with aquatic macrophytes [8,[44][45][46][47][48][49]. The results of the growth characteristics and feed consumption of C. carpio var.…”
Section: Discussionsupporting
confidence: 92%
“…It also recommended that fermented water hyacinth to be used at levels greater than 30% as it influences fish growth at this level compared with low levels (<20%; Sadique et al 2018) and this treatment is not required at lower levels (<10%) of incorporation (El-Sayed 2003). Replacement of water hyacinth meal for 20% fishmeal in rohu diet achieved a higher weight gain than feeding up to 40% substitution level (Patel et al 2016). Eichhornia meal can be incorporated in the diet of L. rohita fingerlings at 15% level without having an adverse effect on the growth and dry matter of fish, and palatability of the feed (Debnath et al 2018).…”
Section: Eichhorniamentioning
confidence: 99%
“…Replacement of water hyacinth meal for 20% fishmeal in rohu diet achieved a higher weight gain than feeding up to 40% substitution level (Patel et al . 2016). Eichhornia meal can be incorporated in the diet of L. rohita fingerlings at 15% level without having an adverse effect on the growth and dry matter of fish, and palatability of the feed (Debnath et al .…”
Section: Macrophytes As Fish Feedmentioning
confidence: 99%